David Lynch : dos mundos extraños (dossier, 2a parte) - Sala, Angel; Alarcón, Tonio L.; Navarro, Antonio José, 1966-; Freixas, Ramón; Bassa, Joan; Barnés, Héctor G.; Salgado, Diego; Casas, Quim, 1959-
Dossier( 2a. parte), en el que reivindica la obra del cineasta americano David Lynch.